MENINGKATKAN HASIL BELAJAR DAN AKTIVITAS SISWA MENGGUNAKAN MODEL PICTURE AND PICTURE BERBANTUAN HANDOUT MATERI ORGANISASI KEHIDUPAN - Yahya, M.; Ningsih, Kurnia; ., Yokhebed (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
This research aims to improve learning achievement and students activities in biology at the organization of life material using the cooperative model picture and picture aided handout. The form of this research is classroom action research, which consists of three cycles with the planning, action, observation and reflection. The result of research showed which has an improvement of passing grade between cycle 1, 2 and 3 were 7.14% and 14.28%. And which has an improvement of student activities between cycle 1, 2 and 3 were 2.73% dan 13.63%. The implementation of cooperative learning model of picture and picture-aided handout can be an alternative learning school biology because it can improve learning achievement and students activities.Keywords: cooperative model picture and picture aided handout, learning achievement, students activities